The link between self-perceptions of aging, cancer view and physical and mental health of older people with cancer: A cross-sectional study. Issue 1 (January 2017) - Schroyen, Sarah; Marquet, Manon; Jerusalem, Guy; Dardenne, Benoît; Van den Akker, Marjan; Buntinx, Frank; Adam, Stéphane; Missotten, Pierre
Abstract: Objectives: Older people may suffer from stigmas linked to cancer and aging. Although some studies suggested that a negative view of cancer may increase the level of depression, such an association has never been studied in the elderly population. Similarly, even though it is established that a negative self-perception of aging has deleterious consequences on mental and physical health in normal aging, the influence in pathological contexts, such as oncology, has not been studied. The main aim of this study is thus to analyze the effect of these two stigmas on the health of elderly oncology patients. Materials and Methods: 101 patients suffering from a cancer (breast, gynecological, lung or hematological) were seen as soon as possible after their diagnosis. Their self-perception of age, cancer view and health (physical and mental) was assessed. Results: Multiple regressions showed that patients with a more negative self-perception of aging and/or more negative cancer view reported poorer global health. We also observed that negative self-perception of aging was associated with worse physical and mental health, whereas negative cancer views were only linked to worse mental health. No interaction was observed between these two stigmas, suggesting that their action is independent. Conclusion: Older patients with cancer face double stigmatization, due to negative self-perception of aging and cancer, and these stigmas have impacts on global and mental health. Self-perception of aging is also linked to physical health. Longitudinal studies will be necessary to analyze the direction of the association between this double stigmatization and health.